A didactic sequence as experience for the development of authentic writing practices (2017)
Introduction: This article is the result of the application of a didactic sequence to the 11 th grade of the “Institución Educativa Manuel Elkin Patarroyo” of the city of Girardot. In the initial route of the didactic sequence the students carried out activities to motivate writing. At the heart of the development of the sequence, a novel narrative emerged from the question, “How do you want your world to be after your graduation?” The theoretical framework is based on the theories of Sergio Tobón and Daniel Cassany, among others, as an updated contribution to the needs of the processes of textual production written in the 21st century. Methodology: Activities were advanced gradually from the elementary to the complex and, in turn, are accompanied by a process of formative evaluation that facilitates the development of skills and achieves important reflections processes. Results: The texts were compiled and a book was prepared (ready for publication) with a total of twenty-nine authors. Conclusions: This set of strategies and processes strengthened the students’ competence with the production of written text in addition to broadening their understanding of its context thanks to authentic writing.